2004
DOI: 10.1159/000079620
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin for the Treatment of Genital Pain Syndromes

Abstract: Our purpose was to test the effect of botulinum toxin injections on hypertonic pelvic floor muscles of patients suffering from genital pain syndromes. We report two cases of women complaining of a genital pain syndrome resistant to pharmacological therapies and rehabilitation exercises associated with a documented involuntary tonic contraction of the levator ani muscle as a defense reaction triggered by vulvar pain. We performed botulinum toxin injections into the levator ani with the intent to relieve pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…There was fair evidence of a lack of efficacy for botulinum toxin injections. [33][34][35][36][37] The body of evidence for other injections was poor; there was insufficient evidence regarding: steroid and "caine"-drug mixed injections, 38,39 multilevel nerve blocks, 40 intramuscular interferon, 41,42 and intralesional interferon. 43,44 Topical Applications.…”
Section: Vestibulodynia Resultsmentioning
confidence: 99%
“…There was fair evidence of a lack of efficacy for botulinum toxin injections. [33][34][35][36][37] The body of evidence for other injections was poor; there was insufficient evidence regarding: steroid and "caine"-drug mixed injections, 38,39 multilevel nerve blocks, 40 intramuscular interferon, 41,42 and intralesional interferon. 43,44 Topical Applications.…”
Section: Vestibulodynia Resultsmentioning
confidence: 99%
“…Studies utilizing transvaginal injection of trigger points are limited but predominantly include the attempts at relief of levator ani muscle spasm using botulinum Neurourology and Urodynamics DOI 10.1002/nau toxin A, utilizing the theory that paralysis of a spastic levator muscle will relieve pain [Romito et al, 2004;Fitzgerald et al, 2005;Thomson et al, 2005]. A study by Jarvis et al [2004] showed signi¢cant improvement on VAS in 12 women with the use of botulinum toxin A using three di¡erent dilutions [Thomson et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient also responded well to 3-monthly repeated BT-A injections. In vaginismus and genital pain syndromes, local BT-A treatment relieves spasms [3, 6,11]. Possible reasons why our patient had a shorter-lasting response to BT-A than previously reported cases (3 months versus > 12) [6] could be that we injected BT-A at a lower dose or she had more severe LA spasms because of abnormal motor inhibitory mechanisms.…”
mentioning
confidence: 77%